Establishing species boundaries in Bornean geckos - Hayden R., Davis; Henry T., Sanford; Indraneil, Das; Izneil, Nashriq; Adam D., Leaché (Royal Society London, 2024)
Species delimitation using mitochondrial DNA (mtDNA) remains an important and accessible approach for discovering and delimiting species. However, delimiting species with a single locus (e.g. DNA barcoding) is biased towards overestimating species diversity. The highly diverse gecko genus Cyrtodactylus is one such group where delimitation using mtDNA remains the paradigm. In this study, we use genomic data to test putative species boundaries established using mtDNA within three recognized species of Cyrtodactylus on the island of Borneo. We predict that multi-locus genomic data will estimate fewer species than mtDNA, which could have important ramifications for the species diversity within the genus. We aim to (i) investigate the correspondence between species delimitations using mtDNA and genomic data, (ii) infer species trees for each target species, and (iii) quantify gene flow and identify migration patterns to assess population connectivity. We find that species diversity is overestimated and that species boundaries differ between mtDNA and nuclear data. This underscores the value of using genomic data to reassess mtDNA- based species delimitations for taxa lacking clear species boundaries. We expect the number of recognized species within Cyrtodactylus to continue increasing, but, when possible, genomic data should be included to inform more accurate species boundaries.